Reliability Centered Maintenance di PT. X - Olivia Sigit; Siana Halim (Jurnal Titra, 2015)
The breakdown machines in the production process at PT. X especially in the Material Mixture Division are occurred quite often. During January to February 2015, those machines 23 times (22.5%) are breakdowns. Therefore, the objective of this research is to design the right maintenance strategy in particularly for machines which have longest downtime. Reliability Centered Maintenance (RCM) with Dempster-Shafer approach is used to solve this problem, since the company does not have historical data. As the results, replacement and condition based maintenance are chosen. Those strategies are the most appropraite and possible ones strategies to be applied in PT. X.